Reproductive behaviour of the black-striped pipefish Syngnathus abaster (Pisces; Syngnathidae) - Silva, K. (2006)
The reproductive behaviour of Syngnathus abaster is described and compared with those of other syngnathids. The need for standardized behavioural data is discussed in light of the actual theories of evolution of mating patterns and sex-role reversal within this family.